Continuous Multi-DoF Wrist Kinematics Estimation Based on a Human–Machine Interface With Electrical-Impedance-Tomography - Zheng, Enhao; Zhang, Jingzhi; Wang, Qining; Qiao, Hong (Frontiers in Neurorobotics, 2021)
This study proposed a multiple degree-of-freedom (DoF) continuous wrist angle estimation approach based on an EIT interface. The interface can inspect the spatial information of deep muscles with a soft elastic fabric sensing band, extending the measurement scope of the existing muscle-signal-based sensors. The designed estimation algorithm firstly extracted the mutual correlation of the EIT regions with a kernel function, and secondly used a regularization procedure to select the optimal coefficients. We evaluated the method with different features and regression models on 12 healthy subjects when they performed six basic wrist joint motions. The average root-mean-square error of the 3-DoF estimation task was 7.62°, and the average R2 was 0.92. The results are comparable to state-of-the-art with sEMG signals in multi-DoF tasks. Future endeavors will be paid in this new direction to get more promising results.